Multiple roles of hypoxia in bovine corpus luteum - Ryo NISHIMURA; Kiyoshi OKUDA (The Society for Reproduction and Development, 2020)
There has been increasing interest in the role of hypoxia in the microenvironment of organs, because of the discovery of hypoxia-inducible factor-1 (HIF1), which acts as a transcription factor for many genes activated specifically under hypoxic conditions. The ovary changes day by day during the estrous cycle as it goes through phases of follicular growth, ovulation, and formation and regression of the corpus luteum (CL). These phenomena are regulated by hypothalamic and pituitary hormones, sex steroids, peptides and cytokines, as well as oxygen conditions. Hypoxia strongly induces angiogenesis via transcription of a potent angiogenic factor, vascular endothelial growth factor (VEGF), that is regulated by HIF1. A CL forms with a rapid increase of angiogenesis that is mainly induced by HIF1-VEGF signaling. Hypoxia also contributes to luteolysis by down-regulating progesterone synthesis and by up-regulating apoptosis of luteal cells. This review focuses on recent studies on the roles of hypoxia- and HIF1-regulated genes in the regulation of bovine CL function.